High‐Pressure‐Mediated Asymmetric Organocatalytic Hydroxyalkylation of Indoles with Trifluoromethyl Ketones. Issue 18 (31st August 2016) - Kasztelan, Adrian; Biedrzycki, Michał; Kwiatkowski, Piotr
Abstract: An enantioselective hydroxyalkylation of indoles and 7‐azaindole with trifluoromethyl ketones was found to be effectively promoted under high‐pressure conditions with a low loading of Cinchona alkaloids (e.g., 1–3 mol% of cinchonidine). Chiral tertiary alcohols containing a trifluoromethyl group were obtained at 9 kbar with good yield and enantioselectivity up to 89%, whereas usually merely traces of products were detected at atmospheric pressure. Abstract :